ULTRASOUND MEASUREMENT OF FETAL KIDNEY LENGTH IN MORMAL PREGNANCY AND ITS CORRELATION WITH GESTATIONAL AGE - Cinnusamy, Maheswari; Shastri, Deepti; Martina, Josephine Arokia (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
An accurate gestational age (GA) is essential for the diagnosis of fetal growth and for planning the exact labour date which provides a better maternity care. Compared with the traditional methods of dating pregnancy using LMP and other clinical measurements, ultrasonographic dating has been recognized as the most accurate method of assessing GA. Any inaccuracy in estimation of  GA lead to perinatal morbidity and mortality due to iatrogenic pre or post maturity.This study aimed to evaluate the accurate GA and precise scheduling of EDD by measuring FKL parameters using USG guided electronic calibration. This prospective study was carried out in 63 women with single uncomplicated pregnancy over a period of 1 year in Arogya Madha Hospital- Gengavalli, after getting an informed consent.  Fetal Kidney Length (FKL) and BPD, FL, HC and AC were measured between 24th-28th week of gestation by using USG (Linear array Transducer). All the parameters were measured by using Electronic calipers, repeated twice and the mean values were calculated to reduce experimental variation. A t-test performed for comparing right and left kidney and it revealed that there is no difference in the length between rightt and left Kidneys. Paired Two Sample for Means P(T<=t) two-tail 0.21813301. In the present study, the FKL correlated with the GA with a correlation coefficient of 0.17157906 and a determination coefficient of 0.822 which was better than all the conventional parameters used. The study shows good correlation between gestational age derived from FKL and gestational age from established biometric indices like BPD, HC, AC, and FL. Keywords:  gestational age, ultrasound,kidney length